Cost description of clinical examination and MRI in wrist ligament injuries. Issue 1 (2nd January 2018) - Andersson, Jonny K.; Hansson-Olofsson, Elisabeth; Karlsson, Jón; Fridén, Jan
Abstract: Objective: The total number and cost of wrist MRIs in the catchment area of the Västra Götaland Region in Sweden (population 1 723 000) during 1 year was analysed, together with the number and content of referrals. Methods: Six radiology departments reported the numbers and rate of all MRI investigations intended to diagnose wrist ligament injuries ( n = 411) and other injuries to the wrist. Results: The additional cost of the difference between MRIs and a clinical examination by a hand surgeon, plus indirect costs for patients with suspected wrist ligament injuries, was calculated as 957 000 euros. Conclusions: It is recommended that MRI should only be used in patients in whom there are clinical difficulties in terms of diagnosing wrist ligament injuries. It is suggested that patients with suspected wrist ligament injuries should be referred directly to an experienced hand surgeon, capable of performing a standardised wrist examination and, when needed, diagnostic arthroscopy and final treatment. The proposed algorithm for the diagnosis and treatment of suspected wrist ligament injuries presented in the present study could save time for the patient and for the radiology departments, as well as reducing costs. The ability to implement the early and appropriate treatment of acute ligament injuries could be improved at the same time.